ANALYSIS OF THE INFLUENCE OF TAX AVOIDANCE, FAMILY MEMBERS BOARDS, AND FOREIGN MEMBERS BOARDS ON THE SOCIAL RESPONSIBILITY OF COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Sinta Arieta (Universitas Internasional Batam, 2024)
The purpose of this writing is to determine the factors that influence corporate social responsibility in Indonesia. Several factors can affect corporate social responsibility including tax evasion, family members and foreign members. This writing takes samples from the annual and financial reports of all corporate sectors that publish sustainability reports and are listed on the Indonesian stock exchange from 2017-2021. The research method used was purposive sampling, with the condition that the report must disclose corporate social responsibility in reports for five consecutive years. The results of the study prove that the board of foreign members has a positive and significant effect on corporate social responsibility. Meanwhile, tax avoidance and family member councils have no effect on corporate social responsibility